2017
DOI: 10.1016/j.ejca.2017.03.030
|View full text |Cite
|
Sign up to set email alerts
|

The 30-year experience—A meta-analysis of randomised and high-quality non-randomised studies of hyperthermic intraperitoneal chemotherapy in the treatment of gastric cancer

Abstract: Importance Hyperthermic intraperitoneal chemotherapy (HIPEC) has been employed within various multimodality strategies for the prevention and treatment of gastric cancer peritoneal carcinomatosis. Objective To systematically evaluate the role of HIPEC in gastric cancer and clarify its effectiveness at different stages of peritoneal disease progression. Data Sources Medline and Embase databases between January 1, 1985, and June 1, 2016. Study Selection Randomized control trials (RTC) and high-quality nonr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
152
1
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 170 publications
(167 citation statements)
references
References 42 publications
5
152
1
9
Order By: Relevance
“…For patients with extensive PM, the completeness of cytoreductive surgery is a critical prognostic factor for survival [6]. This was also shown in a previous meta-analysis [30].…”
Section: Results Of Cytoreductive Surgery and Hipecsupporting
confidence: 56%
See 1 more Smart Citation
“…For patients with extensive PM, the completeness of cytoreductive surgery is a critical prognostic factor for survival [6]. This was also shown in a previous meta-analysis [30].…”
Section: Results Of Cytoreductive Surgery and Hipecsupporting
confidence: 56%
“…The 30-year experience of the HIPEC in the treatment of advanced stage GC with and without PM, has been compared with standard oncological management in a metaanalysis of randomized and high quality non-randomized studies [6]. The comparison has demonstrated the survival advantage of the use of HIPEC as a prophylactic strategy and suggested that patients whose disease burden is limited to positive cytology and limited nodal involvement may benefit the most from HIPEC.…”
Section: Current Issues In Pharmacy and Medical Sciencesmentioning
confidence: 99%
“…When perioperative chemotherapy and perioperative chemotherapy and HIPEC subgroups were compared, there was no statistical difference. This finding suggests that the real benefit for these subjects was from neoadjuvant chemotherapy, as noted in a recent metanalysis, 22 and not from HIPEC. Our study has significant limitations.…”
Section: Group Comparisonmentioning
confidence: 55%
“…Personnel turning over the room should pour solidifier powder into the canisters and perfusion pump reservoir container to render the contents gelatinous and prevent a spill during transport. This waste should never be flushed into the sewer system . Because fluid management systems are docked at a station to be flushed and cleaned before the fluid is released into the water sewage system, they are not an appropriate fluid collection device for HIPEC procedures.…”
Section: Or Cleanup and Turnovermentioning
confidence: 99%
“…This waste should never be flushed into the sewer system. 27,59 Because fluid management systems are docked at a station to be flushed and cleaned before the fluid is released into the water sewage system, they are not an appropriate fluid collection device for HIPEC procedures. Perioperative nurse leaders should refer to their state regulations, hospital policies, and contracted linen service and waste management companies to determine proper handling of surgical supply waste (eg, drapes, gowns, gloves) and cytotoxic contaminated linen.…”
Section: Or Cleanup and Turnovermentioning
confidence: 99%